Palladium-Mediated Reductive Heck Cyclization for the Synthesis of Fused Retinoid Derivatives - Mitra, Trisha; Joardar, Soumen; Chakravorty, Santanu; Majumdar, Manoj; Kundu, Mrinalkanti; Roy, Brindaban (SynOpen, 2023)
Linearly fused retinoid derivatives have been synthesized via a straightforward pathway using a palladium-catalyzed reductive Heck cyclization strategy. The synthesis involved a four-step linear approach utilizing iodination, sulfonylation or benzylation or esterification, palladium-catalyzed Sonogashira cross-coupling and palladium-mediated reductive Heck cyclization.
Keywords: retinoids; Heck; Sonogashira; cross-coupling